Entanglements of the Maghreb : Cultural and Political Aspects of a Region in Motion - Dihstelhoff, Julius; Pardey, Charlotte; Ouaissa, Rachid; Pannewick, Friederike (2021)
The impulse for the recent transformations in the Arab world came from the Maghreb. Research on the region has been on the rise since, yet much remains to be done when it comes to interdisciplinary comparative research. The Maghreb is a heterogeneous region that deserves thorough investigation. This volume focuses on Entanglements as a cross-field and cross-lingual concept to generate a new approach to the region and its inner interdependencies as well as exchanges with other regions. Eminent researchers conceptualize Entanglements through the description of various thematic fields and actors in motion, addressing culture, politics, social affairs, and economics.